Clinical outcomes of a percutaneous cholecystostomy for acute cholecystitis: a multicentre analysis. Issue 7 (19th November 2012) - Sanjay, Pandanaboyana; Mittapalli, Devender; Marioud, Aseel; White, Richard D; Ram, Rishi; Alijani, Afshin
Abstract Background The aim of this study was to review a series of consecutive percutaneous cholecystostomies (PC) to analyse the clinical outcomes. Methods All patients who underwent a PC between 2000 and 2010 were reviewed retrospectively for indications, complications, and short‐ and long‐term outcomes. Results Fifty‐three patients underwent a PC with a median age was 74 years (range 14–93). 92.4% (n = 49) of patients were American Society of Anesthesiologists (ASA) III and IV. 82% (43/53) had ultrasound‐guided drainage whereas 18% (10/53) had computed tomography (CT)‐guided drainage. 71.6% (n = 38) of PC's employed a transhepatic route and 28.4% (n = 15) transabdominal route. 13% (7/53) of patients developed complications including bile leaks (n = 5), haemorrhage (n = 1) and a duodenal fistula (n = 1). All bile leaks were noted with transabdominal access (5 versus 0, P = 0.001). 18/53 of patients underwent a cholecystectomy of 4/18 was done on the index admission. 6/18 cholecystectomies (33%) underwent a laparoscopic cholecystectomy and the remaining required conversion to an open cholecystectomy (67%). 13/53 (22%) patients were readmitted with recurrent cholecystitis during follow‐up of which 7 (54%) had a repeated PC. 12/53 patients died on the index admission. The overall 1‐year mortality was 37.7% (20/53). Conclusions Only a small fraction of patients undergoing a PC proceed to a cholecystectomy with a high risk of conversion to an open procedure. A quarter of patients presented with recurrent cholecystitis during follow‐up. The mortality rate is high during the index admission from sepsis and within the 1 year of follow‐up from other causes.